2009
DOI: 10.1016/j.gca.2009.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of possible source markers in marine dissolved organic matter using ultrahigh resolution mass spectrometry

Abstract: Marine dissolved organic matter (DOM) is one of the most heterogeneous and largest pools of reactive carbon on earth, rivaling in mass the carbon in atmospheric carbon dioxide. Nevertheless, the molecular-level composition of marine DOM has eluded detailed description, impeding inquiry into the specific mechanisms that add or remove compounds from the DOM pool. Here we describe the molecular-level composition of C 18 -extracted DOM along an eastwest transect of the North Atlantic Ocean. We examine the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
185
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(196 citation statements)
references
References 72 publications
(83 reference statements)
8
185
3
Order By: Relevance
“…Uniform depth distributions of DOC have also been reported for the Southern Ocean (Wedborg et al, 1998;Wiebinga and de Baar, 1998;Ogawa et al, 1999) and are consistent with our constantly low wa H/C and high I DEG values. The uniform wa H/C ratios are unusual for ocean depth profiles (Kujawinski et al, 2009;Flerus et al, 2012;Hertkorn et al, 2013) but have been also reported by Koch et al (2005) for the southwestern Weddell Sea. Low H/C ratios and high I DEG values in the deep East Atlantic Ocean compared to the surface waters have been interpreted as a signature of reworked and degraded organic matter (Flerus et al, 2012).…”
Section: Ft-icr Ms Age Model Validationsupporting
confidence: 71%
See 1 more Smart Citation
“…Uniform depth distributions of DOC have also been reported for the Southern Ocean (Wedborg et al, 1998;Wiebinga and de Baar, 1998;Ogawa et al, 1999) and are consistent with our constantly low wa H/C and high I DEG values. The uniform wa H/C ratios are unusual for ocean depth profiles (Kujawinski et al, 2009;Flerus et al, 2012;Hertkorn et al, 2013) but have been also reported by Koch et al (2005) for the southwestern Weddell Sea. Low H/C ratios and high I DEG values in the deep East Atlantic Ocean compared to the surface waters have been interpreted as a signature of reworked and degraded organic matter (Flerus et al, 2012).…”
Section: Ft-icr Ms Age Model Validationsupporting
confidence: 71%
“…Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) has opened a new analytical window to identify molecular formulae of thousands of marine compounds which are not accessible using standard analytical techniques (e.g., Koch et al, 2005Koch et al, , 2008Hertkorn et al, 2006;Kujawinski et al, 2009;D'Andrilli et al, 2010). Currently, much effort is undertaken to overcome the analytical restrictions of this technique (Kido Soule et al, 2010;Sleighter et al, 2010Sleighter et al, , 2012Tfaily et al, 2011) and to refine the data evaluation algorithms (Kujawinski and Behn, 2006;Koch et al, 2007;Flerus et al, 2011;Tziotis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most molecular formulae with positive correlations to the first canonical axes of salinity (Figures 5c and d) and DNA ( Figure 6a) were relatively saturated (H/C ratio of 41), which is typical for marine DOM (Koch et al, 2005;Sleighter and Hatcher, 2008;Kujawinski et al, 2009;Medeiros et al, 2015). Some combustionderived condensed aromatic compounds ('black carbon', very low H/C and O/C ratios) also partially correlated with the canonical axis of DNA.…”
Section: Identifying the Key Factors-dom Moleculesmentioning
confidence: 91%
“…Three studies have looked specifically at interactions between DOM and SAR11, the most abundant marine bacterioplankton clade, and demonstrate the potential for identifying DOM source markers (Kujawinski et al 2009), trophic strategies (Malmstrom et al 2005), and environmental adaptations (GĂłmez-Pereira et al 2012) of specific heterotrophic bacterioplankton taxa. The degradation of a few specific organic compounds have been tracked in-situ using molecular techniques, revealing succession patterns within individual heterotrophic functional groups and highlighting the extreme complexity of microbe-DOM interactions in nature (Lau et al 2007, Watanabe et al 2012.…”
Section: An Interdisciplinary Approachmentioning
confidence: 99%
“…Dissolved organic matter recovered by solid phase extraction (SPE) from spent culture media (hereafter referred to as phytoplankton DOM, or DOM P ) was analyzed by high performance liquid chromatography-electrospray ionization mass spectrometry (HPLC-ESI-MS). Similar untargeted metabolomics approaches have been successfully employed to study many aspects of microbial interactions with DOM (Kujawinski et al 2009, Barofsky et al 2010), but none have yet examined the relationship between DOM composition and the taxonomy of the source organisms. We obtained and analyzed a complex data set comprised of hundreds to thousands of metabolites from each organism tested to compare features produced by different phytoplankton strains.…”
Section: Introductionmentioning
confidence: 99%